Regulation of Alr1 Mg transporter activity by intracellular magnesium. - Phaik Har Lim; Nilambari P Pisat; Nidhi Gadhia; Abhinav Pandey; Frank X Donovan; Lauren Stein; David E Salt; David J Eide; Colin W MacDiarmid (PLoS ONE, 2011)
Mg homeostasis is critical to eukaryotic cells, but the contribution of Mg transporter activity to homeostasis is not fully understood. In yeast, Mg uptake is primarily mediated by the Alr1 transporter, which also allows low affinity uptake of other divalent cations such as Ni(2+), Mn(2+), Zn(2+) and Co(2+). Using Ni(2+) uptake to assay Alr1 activity, we observed approximately nine-fold more activity under Mg-deficient conditions. The mnr2 mutation, which is thought to block release of vacuolar Mg stores, was associated with increased Alr1 activity, suggesting Alr1 was regulated by intracellular Mg supply. Consistent with a previous report of the regulation of Alr1 expression by Mg supply, Mg deficiency and the mnr2 mutation both increased the accumulation of a carboxy-terminal epitope-tagged version of the Alr1 protein (Alr1-HA). However, Mg supply had little effect on ALR1 promoter activity or mRNA levels. In addition, while Mg deficiency caused a seven-fold increase in Alr1-HA accumulation, the N-terminally tagged and untagged Alr1 proteins increased less than two-fold. These observations argue that the Mg-dependent accumulation of the C-terminal epitope-tagged protein was primarily an artifact of its modification. Plasma membrane localization of YFP-tagged Alr1 was also unaffected by Mg supply, indicating that a change in Alr1 location did not explain the increased activity we observed. We conclude that variation in Alr1 protein accumulation or location does not make a substantial contribution to its regulation by Mg supply, suggesting Alr1 activity is directly regulated via as yet unknown mechanisms.